Penyidikan Tindak Pidana Pencabulan Kepada Anak Di Kepolisian Resor Kota Pekanbaru - Muhammad Tuah; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Child is the biggest gift for family, religion, nation and country. She was born to new generation and continue ambitions the nation. And human resources to national building for protect child authorities so there was constatiun about it. It is constatiun No. 23 tahun 2002. One of the steps to protect child is investigation that do it by investigator in the dissoluto case to get authorities child as a sacrifice criminal. In this case investigator must serve to herself in order to she get her authorities. The purpose of skripsion, first, to know investigation that do it by police resort town Pekanbaru second, to found some problem during investigating process that do it by police resort town Pekanbaru third, to get solve problem in this dissolute case in police resort town Pekanbaru.This research categorize yuridis and sosiologis research, because the writer get the data from location that give describing completely source of datas are primer, skunder and tertier datas. Collecting datas are interview and reading the literatures. From the result of research, there are there result can summarizing, first investigating do it by investigator hasn’t pin the procedure second problem in the investigating process is a difficult problem because suspect run a way and sacrifice silent.Third, to solve the problem, investigator give psychologish give suspect status, look for information from other witness. Suggestion of the researcher to investigator to do child dissolute case, investigating quickly and get to solve problem and catch a suspect criminal.Keywort: investigation, criminal, child, prostitute